Etiology of Disease and Traditional Medicine in the Minangkabau Ethnic Cosmology System - Syahrizal Syahrizal; Robi Mitra (Universitas Andalas, 2024)
Traditional medicine still has an important role in overcoming health problems in some Indonesian people, especially in people who live far from the reach of modern medical health services, such as Nagari Maek, Regency 50 Kota of West Sumatra Province. The relationship between the etiology of disease and the use of traditional medicinal herbs and plants by battra (people who heal) in the Minangkabau tribe needs to be explained. This research examines the etiology of disease related to disease symptoms, causes, concepts of health and disease, as well as physical treatment of sick people. This research was conducted in the Nagari Maek community, Regency 50 Kota with 5 informants, 10 of whom were patients or had been patients. The research uses ethnographic type qualitative methods, namely observation, in-depth interviews and documentation. The results of the research show that the diseases that occur in the Nagari Maek community are caused by personalistic causes (diseases caused by the supernatural through shamans who aim to cause disease) and naturalistic causes (diseases caused by food, unclean environments, conditions in a person's body such as blood clogged, blood not flowing smoothly and so on). Diseases caused by personalism, in general, battra perform external treatment by soaking the concoction and sprinkling it on the patient's body, distributing the air concoction throughout the sick person's body and emitting smoke from the concoction into the patient's body. Meanwhile, diseases caused by naturalistic causes are treated by using concoctions that have been made to be drunk or eaten by the patient being treated.